Art meets Ads - Harten, Jürgen; Schirner, Michael; Kunsthalle, Düsseldorf (Stuttgart : Edition Cantz, 1993)
Bickerton, Ashley ; Richter, Gerhard ; Locher, THomas ; Ponjuan, Eduardo ; Francisco, René ; Eichhorn, Maria ; Slominski, Andreas ; Kruger, Barbara ; Grünfeld, Thoams ; Adams, Dennis ; Koons, Jeff ; Lawler, Louise ; Blum, Heinr ; etc.
Art meets Ads, Kunst trifft Werbung in der Ausstellung "Avantgarde & Kampagne", Kunsthalle Düsseldorf, 18. - 27. September 1992
boek